Winter according to Humphrey - Birney, Betty G. (Birney, Betty G. Humphrey adventures, 2013)
"The holidays are coming and Humphrey is unsqueakably excited. He loves to hear about all the different ways his friends in Room 26 celebrate and to watch them make costumes and learn songs for the Winter Wonderland pageant. (He even squeaks along!) But with so much to do, will the holidays go according to plan? Do-It-Now-Daniel is having trouble practicing, Helpful-Holly can't stop worrying about making presents for her friends, and Humphrey still has to find a gift for Og! Good thing Humphrey is one smart hamster who can help them all fill the season with JOY-JOY-JOY!"--Back cover.